(3TQM GdLOhd GdLGeY ddCUhds - (3eLghds
(3ChdgG (B:s
(3GYde Cf deG ef Gddg JYGdi ef aVdg Ydi habfi deYQaI gPG GdLOhd GLGeY dPj YLRJ GdYbdGA Yf ageg deG ajg ef GdYLGFH s
(3BNQgG (B:s
(3UhQI Pdc ceG JQi hGddg JYGdi Hg GdoeSJYGf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B58s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs